2016
DOI: 10.1158/1078-0432.ccr-16-0171
|View full text |Cite
|
Sign up to set email alerts
|

High Intratumoral Stromal Content Defines Reactive Breast Cancer as a Low-risk Breast Cancer Subtype

Abstract: Purpose The current study evaluated associative effects of breast cancer cells with the tumor microenvironment and its influence on tumor behavior. Experimental design Formalin-fixed paraffin embedded tissue and matched protein lysates were evaluated from two independent breast cancer patient data sets (TCGA and MD Anderson). Reverse-phase protein arrays (RPPA) were utilized to create a proteomics signature to define breast tumor subtypes. Expression patterns of cell lines and normal breast tissues were util… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
9
23
0
Order By: Relevance
“…Cluster 5 (reactive) had high levels of MYH11, HSP70, FIBRONECTIN, COLLAGEN VI, CAVEOLIN1 and RICTOR, as well as remarkably low levels of the proapoptotic mediator BAK , perhaps contributing to the cluster’s poor outcomes. Reactive cancer subtypes showed high levels of proteins that are likely produced in the tumor microenvironment as the result of interactions between cancer cells and cells in the microenvironment, including fibroblasts, as discussed previously for reactive breast cancer subtypes (Cancer Genome Atlas Network, 2012; Dennison et al, 2016). …”
Section: Proteomic Analysis By Rppasupporting
confidence: 55%
“…Cluster 5 (reactive) had high levels of MYH11, HSP70, FIBRONECTIN, COLLAGEN VI, CAVEOLIN1 and RICTOR, as well as remarkably low levels of the proapoptotic mediator BAK , perhaps contributing to the cluster’s poor outcomes. Reactive cancer subtypes showed high levels of proteins that are likely produced in the tumor microenvironment as the result of interactions between cancer cells and cells in the microenvironment, including fibroblasts, as discussed previously for reactive breast cancer subtypes (Cancer Genome Atlas Network, 2012; Dennison et al, 2016). …”
Section: Proteomic Analysis By Rppasupporting
confidence: 55%
“…In the TCGA study however, Collagen VI is well represented in Cluster_V notable for a reactive/EMT signature and better relapse-free survival when compared to other clusters [7]. Additionally, Dennison et al recently identified a similarly reactive subtype of breast cancer by RPPA notable for high stromal content similarly associated with favorable outcomes [11]. Our findings are concordant with improved outcomes in high Collagen VI CRC expression [HR= 0.31 (95% CI 0.15, 0.65; p= 0.002)].…”
Section: Discussionmentioning
confidence: 99%
“…However, these portend an adverse prognosis in triple negative tumors [11]. Dennison et al recently discovered that a particular stromal protein signature in breast carcinoma is associated with a highly differentiated phenotype [50]. The outcome analysis in our study identified significant correlation between ColXα1/elastin expression in the neoadjuvant-treated tumor but not in the adjuvant setting.…”
mentioning
confidence: 44%